类可可脂原料油中低熔点甘油三酯的组成、 含量调控与综合利用Composition, content regulation and comprehensive utilization of low-melting triglycerides in cocoa butter equivalent raw oils - 刘陈钰，甄铖，郑小宇，王颖琪，王雨昕，金俊，金青哲，王兴国 LIU Chenyu, ZHEN Cheng, ZHENG Xiaoyu, WANG Yingqi, WANG Yuxin, JIN Jun, JIN Qingzhe, WANG Xingguo (Zhongguo youzhi, 2023)
为了实现类可可脂在巧克力中更为高效的应用，降低其对产品品质的影响，综述了类可可脂原料油中低熔点甘油三酯的组成与熔化性质，概括了不同种类甘油三酯对巧克力霜变行为的作用特征；进一步讨论了控制低熔点甘油三酯含量的技术方法，包括基因工程和分提；最后，总结了经分提获得的低熔点成分的再利用。类可可脂原料油中低熔点甘油三酯可能对巧克力的制造（尤其是调温）和质量控制（如软化、起霜等）产生不利影响。通过分提选择性降低低熔点甘油三酯含量是制备高品质类可可脂的优选路径。In order to achieve a more efficient application of cocoa butter equivalent in chocolate and to reduce their impact on product quality, the composition and melting properties of low-melting triglycerides in cocoa butter equivalent raw oils were reviewed, and the effects of different types of triglycerides on the frosting behavior of chocolate were summarized. The technological methods for controlling the content of low-melting triglycerides were further discussed, including genetic engineering and fractionation, and the reuse of low-melting triglycerides obtained by fractionation was summarized. Low-melting triglycerides in cocoa butter equivalent raw oils may have negative effects on chocolate manufacture (especially tempering) and quality control (softening, and blooming, etc). Reducing the content of low-melting triglycerides by fractionation is the best way to prepare high quality cocoa butter equivalent.